Report on formation of a population of apomictic hybrids through the cross of the elite sexual-synthetic population for recurrent selection and the male tester CIAT 16888 - Ríos, Gonzalo; Espitia, Paula A.; Hernández, Luis Miguel; Castiblanco, Valheria (Bioversity International and the International Center for Tropical Agriculture, 2020)
The new population of hybrids, Uh2020, for the third cycle of recurrent selection of Urochloa humidicola breeding program was obtained from the cross between the apomictic male tester, CIAT 16888, and the sexual genotypes from the BhSx19 population. This was the result of the establishment on field since 2018 of the male tester in 1.5 ha, and the 707 genotypes of the elite sexual-synthetic population BhSx19 transplanted on February 2020. An early flowering peak was observed in the end of May and beginning of June in the crossing field due to the vernalization effect of the site in the mountains (Carrizal, Valle del Cauca, Colombia). The manual harvest was done weekly and lasted 13 weeks until September 14th. As a result, we obtained a better seed production that is intended to be processed, then it was left at room temperature during the dormancy period and stored in a cold room to preserve its viability. The apomictic hybrids can be identified through molecular marker p779/p780.